The Effect of Obliquity‐Driven Changes on Paleoclimate Sensitivity During the Late Pleistocene. Issue 13 (13th July 2018) - Köhler, Peter; Knorr, Gregor; Stap, Lennert B.; Ganopolski, Andrey; de Boer, Bas; van de Wal, Roderik S. W.; Barker, Stephen; Rüpke, Lars H.
Abstract: We reanalyze existing paleodata of global mean surface temperature Δ T g and radiative forcing Δ R of CO2 and land ice albedo for the last 800, 000 years to show that a state‐dependency in paleoclimate sensitivity S, as previously suggested, is only found if Δ T g is based on reconstructions, and not when Δ T g is based on model simulations. Furthermore, during times of decreasing obliquity (periods of land ice sheet growth and sea level fall) the multimillennial component of reconstructed Δ T g diverges from CO2, while in simulations both variables vary more synchronously, suggesting that the differences during these times are due to relatively low rates of simulated land ice growth and associated cooling. To produce a reconstruction‐based extrapolation of S for the future, we exclude intervals with strong Δ T g ‐CO2 divergence and find that S is less state‐dependent, or even constant state‐independent), yielding a mean equilibrium warming of 2–4 K for a doubling of CO2 . Plain Language Summary: Anthropogenic carbon dioxide (CO2 ) emissions will lead to rising global mean temperature through the greenhouse effect. The amplitude of this warming, as estimated with computer simulations for the equilibrium climate response to a doubling of atmospheric CO2 concentration, is called climate sensitivity. It is necessary to verify these simulation‐based quantifications of climate sensitivity with independent alternative approaches. One such approach is the analysis of past (paleo) climates, which has indicated a state‐dependent paleoclimate sensitivity. Here we compare different data‐based reconstructions and computer‐based simulations of paleoclimate sensitivity of the last 800, 000 years and find that they disagree. In data‐based reconstructions global mean temperature and CO2 diverge during intervals when land ice growth is particularly pronounced. This temperature‐CO2 divergence is not observed in simulations, probably due to an underestimation of the rate of land ice growth and the associated cooling. However, these periods of pronounced land ice growth are not of relevance for a warming future and can therefore be neglected when estimating climate sensitivity from reconstructions of the past. Consequently, we find that paleoclimate sensitivity derived from reconstructions is less state‐dependent than previously thought and agrees with warming estimates of 2–4 ° C as derived from simulated equilibrium climate response for CO2 doubling. Key Points: Proxy‐based reconstructions and model‐based simulations of global mean surface temperature over the last 800, 000 years differ in detail During periods of decreasing obliquity and sea level the proxy reconstructions show a temperature‐CO2 divergence missing in simulations Elimination of these periods leads to a more linear paleoclimate sensitivity and to equilibrium warming for CO2 doubling of 2‐4 K